2015
DOI: 10.1016/j.ijsu.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of estrogen receptor β2 in breast cancer

Abstract: Endocrine therapy is provided to all patients with estrogen receptor (ER)-positive breast cancer, but only a subset of them derives clinical benefit. The discovery of ERβ and its five isoforms added another layer of complexity in the regulation of estrogen activity in breast cancer cells. Two large retrospective studies showed conflicting results with regard to the prognostic value of the different ERβ isoforms in patients treated with tamoxifen in an adjuvant setting. This study tested the hypothesis that ERβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…In the cohort presented by Nakopoulou and colleagues, in which patients received adjuvant chemotherapy and/or endocrine therapy, results were similar to our findings (34). As many of the clinical studies were observational studies and patients often received both chemotherapy and endocrine therapy (35,36), it is somewhat surprising that associations between ERb and chemotherapy have been rarely discussed (7,24). The main finding in this study was the impact of ERb1 75 expression on prognosis among patients who received adjuvant chemotherapy, some of whom also received tamoxifen and/or AIs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the cohort presented by Nakopoulou and colleagues, in which patients received adjuvant chemotherapy and/or endocrine therapy, results were similar to our findings (34). As many of the clinical studies were observational studies and patients often received both chemotherapy and endocrine therapy (35,36), it is somewhat surprising that associations between ERb and chemotherapy have been rarely discussed (7,24). The main finding in this study was the impact of ERb1 75 expression on prognosis among patients who received adjuvant chemotherapy, some of whom also received tamoxifen and/or AIs.…”
Section: Discussionsupporting
confidence: 89%
“…Also, scoring systems based on combinations of fraction and intensity have been commonly applied (16,33,(46)(47)(48). Higher cutoffs, such as >20% (12,46,49,50) or higher (33,34,36), have also been applied. One highly cited study applied cutoffs for ERb1 þ that resulted in highly skewed distributions; >95% of the patients had ERb1 þ tumors, and although there was a tendency toward a beneficial effect, it was reported as a null finding (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e ERβ2 isoform is increased in chronic lymphatic leukemia, prostate cancer, non-small-cell lung cancer, breast cancer, and ovarian cancer [35]. e worsening disease-free survival and overall survival of patients were correlated with ERβ2 expression in patients treated with tamoxifen [36]. Moreover, ERβ2 is involved also in the metastasis of prostate cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some studies have demonstrated ERβ positivity to be correlated with a more aggressive clinical outcome15 and with the proliferation marker, Ki-67 43–45. ERβ has also been identified as a novel activator of wild-type p53-dependent transcription, which leads to poorer survival of luminal breast cancer cells 42 46–50…”
Section: Discussionmentioning
confidence: 99%